Analisis Semiotika Iklan Produk Elektronik Handphone di Media Cetak - Linggar, Patrick (Kajian Linguistik, 2018)
The objectives of this research are (1) to identify and analyze the types of semiotic meaning of electronic product advertising on magazine including signified and signifier. (2) to analyze whether there is a relationship between the signifier and signified concerning the expression of the meaning that exists in electronic products mobile advertising in the print media; (3) to determine the rhetorical language and why it is used in electronic product advertising. This research is descriptive qualitative study. The data were taken randomly from three magazine monthly editions June and July 2013 as many as 6 product electronic chosen in which the data were taken in various types of mobile electronic product. In identifying and analyzing the semiotic meaning is used semiotic theory concerning (signified and signifier). It can be concluded that semiotic meaning including the use of icon, index, and symbol also types of language are used especially for marketing product. Additionally, further research on semiotic and its elements in magazine or another media may be pursued that the phenomenon of language use and language aspect can be clearly understood.Keywords : semiotic, icon, index and symbol